POTENSI BAKTERI RHIZOSFER PELARUT FOSFAT SEBAGAI BIOFERTILIZER KOPI ARABIKA (Coffea arabica L) - Alamsyah, Rizky; Armaniar, Armaniar; Wasito, M. (Fakultas Pertanian, Universitas Janabadra, 2023)
Arabica coffee (Coffea arabica L) is one of Indonesia”s mainstay plants to develop the world's largest coffee producer. The high level of demand for coffee bean products requires the provision of large quantities and quality seeds. Nursery is the first step in coffee cultivation which affects productivity and crop production. The latest biofertilizer innovation is to utilize phosphate solubilizing microorganisms as biological fertilizers. This study aims to determine the effect and interaction of the addition of rhizosphere bacterial suspension and bacterial capsules on Arabica coffee plants. The research design used was a completely randomized design (CRD), consisting of 16 treatments with 2 replications. The first factor was the administration of a rhizosphere bacterial suspension consisting of R0:0 .ml, R1:10 ml:R2:20 ml, R3:30 ml and the second factor was the addition of a bacterial capsule consisting of A0:0 gr, A1:10 gr, A2. :20 g, A3:30 g. Isolates from oil palm soil obtained 14 isolates of rhizosphere bacteria. The best observation of plant height was the R3 treatment (24.55 cm). The observation of the number of leaves was R3 (15,25 cm). for the leaf area parameter the highest number was obtained R3 (25.53 cm). The test results showed that the application of suspension microcapsules and rhizosphere bacteria significantly increased the growth of Arabica coffee (Coffea arabica L)Key words: Rhizosphere bacteria, suspension, microcapsules INTISARIKopi arabica (Coffea arabica L) merupakan salah satu tanaman andalan Indonesia dalam perkembangan penghasil kopi terbesar di dunia Tingginya laju permintaan akan produk-produk biji kopi menuntut penyediaan bibit dalam jumlah besar dan berkualitas. Pembibitan merupakan langkah awal dalam pembudidayaan kopi yang berpengaruh terhadap produktifitas dan produksi tanaman. Inovasi pupuk hayati yang terbaru adalah memanfaatkan mikroganisme pelarut fosfat sebagai biofertilizer. Penelitian ini bertujuan untuk mengetahui pengaruh dan intraksi penambahan suspensi bakteri rhizosfer dan kapsul bakteri terhadap tanaman kopi arabica. Rancangan penelitian yang digunakan adalah rancangan acak lengkap ( RAL), terdiri 16 perlakuan dengan 2 ulangan. Faktor pertama adalah pemberian suspensi bakteri rhizosfer yang terdiri dari R0: 0 ml, R1:10 ml: R2:20ml, R3:30 ml dan faktor kedua adalah penambahan kapsul bakteri yang terdiri dari A0: 0 g, A1: 10 g, A2:20 g, A3: 30 g. Isolat dari tanah kelapa sawit diproleh 14 isolat bakteri rhizosfer. Pengamatan tinggi tanaman terbaik adalah perlakuan R3 (24,55 cm) pengamatan jumlah daun adalah A2 (15,25 cm). untuk parameter luas daun angka tertinggi diperoleh R3 (25,53 cm). Hasil pengujian menunjukkan bahwa aplikasi mikrokapsul suspensi dan bakteri rhizosfer secara nyata meningkatkan pertumbuhan tanaman kopi arabica (Coffea arabica L). Kata kunci: Bakteri Rhizosfer, suspensi, mikrokapsul